2013
DOI: 10.1136/amiajnl-2012-001525
|View full text |Cite
|
Sign up to set email alerts
|

An information-gain approach to detecting three-way epistatic interactions in genetic association studies

Abstract: BackgroundEpistasis has been historically used to describe the phenomenon that the effect of a given gene on a phenotype can be dependent on one or more other genes, and is an essential element for understanding the association between genetic and phenotypic variations. Quantifying epistasis of orders higher than two is very challenging due to both the computational complexity of enumerating all possible combinations in genome-wide data and the lack of efficient and effective methodologies.ObjectivesIn this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 41 publications
0
71
0
Order By: Relevance
“…The two metrics are chosen due to their wide applications in the literature, their effectiveness in high-dimensional binary data (Sebastiani & Ricerche, 2002;Sun & Wu, 2008), and also their distinct characteristics. The two metrics were previously used in several bio-data mining applications (Granizo-MacKenzie & Moore, 2013; Hu et al, 2013) and achieved good results. Figure 5 shows an overview of the proposed GP method.…”
Section: The Proposed Gp Approachmentioning
confidence: 87%
“…The two metrics are chosen due to their wide applications in the literature, their effectiveness in high-dimensional binary data (Sebastiani & Ricerche, 2002;Sun & Wu, 2008), and also their distinct characteristics. The two metrics were previously used in several bio-data mining applications (Granizo-MacKenzie & Moore, 2013; Hu et al, 2013) and achieved good results. Figure 5 shows an overview of the proposed GP method.…”
Section: The Proposed Gp Approachmentioning
confidence: 87%
“…Specifically, we used a new measure of three-way epistasis that adjusts for lower-order effects 10. This approach was used to confirm high-order non-additive interactions.…”
Section: Methodsmentioning
confidence: 99%
“…Gene-gene and gene-environment interactions: A number of studies have suggested that TB susceptibility genes interact with each other (Table 1) [7, 20, 22, 25, 36, 37]. When interaction exists between two genes, it is possible that significant main effects may not be observed due to different allele frequencies at the second gene or environmental exposure [38].…”
Section: Previous Genetic Studies Of Tbmentioning
confidence: 99%